Students' Perceptions of History Teaching in Grade XI of Senior High School at SMAN 1 Parigi Tengah - Fauzy Rachmat; Suyuti; Haliadi; Fajar Nugroho (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to determine students' perceptions of History teaching in grade XI of SMA Negeri 1 Parigi Tengah, specifically regarding the teaching methods used by teachers with a background in Geography. This study uses a descriptive qualitative approach conducted in a natural setting. The research subjects consisted of grade XI students, with supporting informants in the form of subject teachers and homeroom teachers. Data collection techniques were carried out through observation, semi-structured interviews, and documentation. Data were analyzed using an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that students' perceptions of History teachers' teaching methods vary. Some students considered the lecture method used to help understanding the material if delivered clearly, coherently, and communicatively. However, some other students felt that the method was less interesting if it was done monotonously and with minimal variation, thus decreasing interest and active learning. The use of learning media was also considered suboptimal, even though supporting facilities were available at the school. Factors that influence students' perceptions include the teacher's ability to deliver the material, the teacher's teaching style and attitude, the suitability of the method to the characteristics of the History material, students' interests and learning styles, and the learning environment. This study concludes that variations in methods and the use of learning media are very necessary to increase students' interest and understanding in learning History.